Bispecific antibodies tethering innate receptors induce human tolerant-dendritic cells and regulatory T cells - Lamendour, Lucille; Gilotin, Mäelle; Deluce-Kakwata Nkor, Nora; Lakhrif, Zineb; Meley, Daniel; Poupon, Anne; Laboute, Thibaut; di Tommaso, Anne; Pin, Jean-Jacques; Mulleman, Denis; Le Mélédo, Guillaume; Aubrey, Nicolas; et al. (Frontiers in Immunology, 2024)
There is an urgent need for alternative therapies targeting human dendritic cells (DCs) that could reverse inflammatory syndromes in many auto-immune and inflammatory diseases and organ transplantations. Here we describe a bispecific antibody (bsAb) strategy tethering two pathogenrecognition receptors at the surface of human DCs. This cross-linking switches DCs into a tolerant profile able to induce regulatory T-cell differentiation. The bsAbs, not parental Abs, induced interleukin 10 and transforming growth factor b1 secretion in monocyte-derived DCs and human peripheral blood mononuclear cells. In addition, they induced interleukin 10 secretion by synovial fluid cells from rheumatoid arthritis and gout patients. This concept of bsAb-induced tethering of surface pathogen recognition receptors switching cell properties opens a new therapeutic avenue for controlling inflammation and restoring immune tolerance.